Trends in Walking for Transportation in the United States, 1995 and 2001 - Sandra A. Ham, MS; Caroline A. Macera, PhD; Corina Lindley, MPH (Centers for Disease Control and Prevention, 2005)
Introduction The purpose of this study was to examine trends in walking for transportation among U.S. adults and youth for Healthy People 2010 objective 22-14. The objective calls for increasing the proportion of trips of 1 mile or less made by walking to 25% for adults and 50% for youth. National transportation surveys are used to track national health objectives, but data interpretation and caveats to use have not been discussed in the public health literature to date. Methods Cross-sectional analyses at two time points used data from the 1995 Nationwide Personal Transportation Survey and the subsequent 2001 National Household Travel Survey. The populations of interest were U.S. civilian noninstitutionalized adults (aged 18 years and older) and youth (aged 5 to 15 years). Trends were reported for the percentage of walking trips of 1 mile or less for transportation (adults) and walking trips of 1 mile or less to school (youth) using 86,286 trips (1995) and 119,462 trips (2001) made by adults and 3114 trips (1995) and 4073 trips (2001) made by youth. Results Of trips of 1 mile or less, adults reported more walking in 2001 (21.2%; 95% confidence interval [CI], 20.5-21.9) than in 1995 (16.7%; CI, 15.9-17.5). For trips to school of 1 mile or less, youths also increased walking from 1995 (31.3%; CI, 27.9-34.4) to 2001 (35.9%; CI, 33.0-38.8). Changes in survey methodology affected the interpretation of the Healthy People 2010 trends. Conclusion In spite of small increases in walking between 1995 and 2001 accompanying a change in survey methodology, U.S. adults and youth fall short of meeting Healthy People 2010 walking objectives for trips of 1 mile or less.